The Impact of Brand Image and Promotion Programs on Customer Loyalty with Customer Satisfaction as a Mediator: A Study of Livin’ by Mandiri Users - Dian Cahyadi; Anies Lastiati Lastiati (Universitas KH. Abdul Chalim Mojokerto, 2026)
The rapid growth of mobile payment services in Indonesia has intensified competition, driven by technological advancements and the growing presence of from both banking and non-banking payment service providers. This study analyzes the effect of brand image and promotion programs on customer loyalty, with customer satisfaction as a mediating variable, focusing on users of the Livin’ by Mandiri application in the Greater Jakarta (Jabodetabek) area. The research employed a quantitative approach using Partial Least Squares Structural Equation Modelling (PLS-SEM) for data analysis. The results show that brand image increases customer satisfaction but does not directly impacts customer loyalty. In contrast, promotion programs significantly affect both customer satisfaction and loyalty. Furthermore, customer satisfaction is found effectively mediate the relationship between brand image and promotion programs on customer loyalty. These results emphisize the strategic importance of strengthening brand image and desining effective promotional strategies to enhance customer satisfaction, which ultimately leads to sustained loyalty among payment users.